Crack-tip shielding by the dilatant transformation of particles/fibers embedded in composite materials. (December 2015) - Li, Qun; Lv, Junnan; Hou, Junling; Zuo, Hong
Highlights: The fracture toughness of the composites, which enhanced by particles or fibers with a specific dilatant transformation occurs, has been studied. The enhanced toughness is attributed to the crack-tip shielding from the residual strain fields, which derive from the transformation of particles or fibers dispersed near the crack tip. The crack-tip shielding is estimated from the reduction of the crack tip J -integral compared to the remote J -integral, which can be elucidated by the configurational forces integrated over the transformation areas. The influence of dilatant transformation on fracture toughness is investigated for one particle, multi-particles, one fiber, multi-fibers, respectively, dispersed in composite materials. A reduction of the crack tip J -integral can be developed by the transformed particles or fibers. Abstract: The fracture toughness can be enhanced by a specific dilatant transformation occurring in particle or fiber-reinforced composites. The enhanced toughness is attributed to the crack-tip shielding from the residual strain fields which develop following the transformation of particles or fibers dispersed near the crack tip. In the present study, the crack-tip shielding is estimated from the reduction of the crack tip J -integral compared to the remote J -integral. The reduction of J -integral can be elucidated by the configurational forces integrated over the transformation areas. The configurational forces are inherently related to the change of the total potential energy due to phase transformation. Numerical analysis is performed for a system with sufficiently small particles or fibers in the fully transformed zone near the crack tip. The influence of dilatant transformation on fracture toughness is investigated for one individual particle, multi-particles, one individual fiber, multi-fibers, respectively, dispersed in composite materials. It is found that a reduction of the crack tip J -integral can be developed by the presence of the dispersed particles or fibers. The crack tip shielding effect is strongly dependent of the location and size of particles or fibers. The larger/longer the particles/fibers are, the greater effect of the transformed particles/fibers on the crack-tip shielding. The present analysis provides a better understanding of the role of dilatant transformed particles/fibers on crack-tip shielding in composite materials.